Bentuk Sediaan dan Keamanan Penggunaan Tea Tree (Melaleuca alternifolia) Oil dalam Kosmetik - Damras, Anggi Aprianti; Mirawati, Mirawati; Hasrawati, Andi (PHARMACY UMI JOURNAL SYSTEM, 2024)
Tea Tree Oil is an essential oil obtained from distillation and has a complexity of active ingredients, a strong aroma, and a natural marketing image that causes it to be frequently used in modern skin care products. This literature study aims to determine the cosmetic dosage form of Tea Tree (Melaleuca alternifolia) Oil and the safety of its use, which was carried out using the article review method using Google Scholar and PubMed as data sources, then journals were selected based on inclusion and exclusion criteria. Relevant articles were selected from as many as 11 articles. The results of the review showed that tea tree oil is widely formulated as a cosmetic preparation in the form of shampoos, toothpaste, hydrogels and bio-polymers with activities as antibacterial, antifungal, antiviral, antiseptic, anti-inflammatory on the skin, and anti-acne. Tea tree oil also shows good safety at certain concentrations, but can also cause allergic reactions.